Analysis of the Effect of Service Quality on Loyalty with Family Satisfaction as an Intervening Variable (A Case Study) - Nursoffa, Idris; Yuliaty, Farida; Malik, Rahadian; Paramarta, Vip; Kosasih, Kosasih; Fitriana, Fitriana (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
At the Regional General Hospital, Drs. Jacobus Luna, M.Si, and Bengkayang examine patient loyalty, family satisfaction, and service quality. In order to increase patient family happiness, hospitals must now offer complete services and uphold patient trust by enhancing service quality. With a sample of 100 respondents who are patients at the Regional General Hospital under the care of Drs. Jacobus Luna and M. Si, Bengkayang, this study takes a quantitative method. Descriptive-verificative analysis along with path analysis was used to analyze the data. Although some issues were found that need to be addressed and improved, respondents rated service quality, patient family satisfaction, and loyalty as good to very good, according to the results of the descriptive analysis. The indirect effect's coefficient was higher than the direct effect's (85.1% > 80.4%), and the path coefficients between the variables were positive, according to the findings of the verifying study utilizing path analysis. This suggests that the relationship between service quality and loyalty can be mediated by the intervening variable of patient family satisfaction. Given that the t-value is higher than the t-critical (26.60 > 1.95), the statistical hypothesis test (t-test) demonstrated that the service quality variable has a positive and substantial impact on patient family satisfaction. Loyalty is positively and significantly impacted by the patient family satisfaction variable (t = 21.39 > 1.95). Additionally, loyalty is positively and significantly impacted by service quality (t = 20.05 > 1.95). Because the t-value is higher than the t-critical (3.81 > 1.95), service quality indirectly influences loyalty through patient family satisfaction.